TAMAN REKREASI AIR DI PONTIANAK UTARA - Lunar, Flavia Tiffany; Purnomo, Yudi; Affrilyno, Affrilyno (JMARS: Jurnal Mosaik Arsitektur, 2025)
Following the COVID-19 pandemic, public awareness of healthy lifestyles and mental health well-being has notably increased. This presents a significant opportunity to create environments that foster innovation in health and wellness, thereby supporting economic growth. However, the limited availability of integrated facilities has become a major obstacle in fulfilling the public"™s need for healthy entertainment and physical activities. Therefore, the design of the North Pontianak Water Park aims to provide a recreational space that supports both aquatic and social activities. The design process implements R. Whitaker"™s eight-step design method, which commences with issue identification and culminates with development of a design concept based on analytical results. The design concept focuses on integrating core functions, including water attractions, social spaces, and supporting facilities. A functional design approach that responds to the local climate while prioritizing comfort, safety, and accessibility. The final design features four buildings with different functions, nine swimming pools in separate zones, one extreme slide, one spiral slide, and five racer slides.